Relevansi Perencanaan Lingkungan Pendidikan Islami dalam Pembentukan Kematangan Emosi Peserta Didik: Kajian Historis dan Konteks Modern - Al Hawari, Sarah Rifat; Rahman, Imas Kania; Lisnawati, Santi (Tarbawi : Jurnal Pendidikan Islam, 2024)
The educational environment plays a crucial role in shaping students' careers and personalities. This is also supported by the Qur'anic verses related to the educational environment. To deepen the urgency of a good educational environment and the successes achieved by Muslim predecessors, research on Islamic historical studies is needed to strengthen the importance of educational planning. This study uses a literature review method, focusing on the Qur'an and relevant historical literatures. The study adopts Sartain's theory of three types of educational environments, correlating these with Qur'anic verses that directly address educational environments. Additionally, this study presents historical examples of successful Islamic educational practices, highlighting figures such as Imam Ahmad bin Hanbal, Salahuddin Al-Ayyubi, and Alp Arslan.The relevance of this study in modern education lies in its ability to address contemporary challenges such as social pressure, technological influence, and changing family values. Islamic historical concepts can offer holistic solutions by integrating intellectual, emotional, and spiritual development within educational planning. The findings emphasize the critical role of educational environments in fostering emotional independence among students, as exemplified by the success of previous Islamic generations. This study contributes to the discourse on adapting Islamic educational principles to modern contexts to develop a well-rounded and emotionally resilient generation.